2021
DOI: 10.1136/bmjoq-2020-001192
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of remote capillary blood testing in an outpatient clinic setting to improve shared decision making and patient and clinician experience: a validation and pilot study

Abstract: BackgroundIn a tertiary respiratory centre, large cohorts of patients are managed in an outpatient setting and require blood tests to monitor disease activity and organ toxicity. This requires either visits to tertiary centres for phlebotomy and physician review or utilisation of primary care services.ObjectivesThis study aims to validate remote capillary blood testing in an outpatient setting and analyse impact on clinical pathways.MethodsA single-centre prospective cross-sectional validation and parallel obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In line with our results, previous studies could demonstrate that UA-based self-sampling is perceived as less painful compared with traditional venous blood collection 28 and finger pricking. 27 Similarly, perceived usability of both devices (SUS: Tasso+: 88.6; TAP II: 86.0) was higher compared with finger pricking (61.0 37 and 80.7 29 ), likely due to automatic blood collection. The NPS (likelihood to promote device) of both devices was as high (+28.6%) as in our previous study, comparing a former Tasso version with finger pricking (Tasso-SST: NPS +28%; finger pricking −20%).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In line with our results, previous studies could demonstrate that UA-based self-sampling is perceived as less painful compared with traditional venous blood collection 28 and finger pricking. 27 Similarly, perceived usability of both devices (SUS: Tasso+: 88.6; TAP II: 86.0) was higher compared with finger pricking (61.0 37 and 80.7 29 ), likely due to automatic blood collection. The NPS (likelihood to promote device) of both devices was as high (+28.6%) as in our previous study, comparing a former Tasso version with finger pricking (Tasso-SST: NPS +28%; finger pricking −20%).…”
Section: Discussionmentioning
confidence: 97%
“…Remote longitudinal serological monitoring could improve early flare detection, 25 reduce clinical visits, 50 offer time-saving for patients and clinicians, empower patients and improve shared decision-making. 37 It would add valuable objective data to complement currently available remote PROs, such as electronic questionnaires 51 and wearable data. 52 Exact quantification of autoantibody levels is currently not clinically relevant for all IMRDs, however, increasing evidence exists for MPO, 9 PR3 8 9 and especially dsDNA, 7 and our study demonstrates clinical utility with very good agreement for PR3 (r=0.9818 (p<0.0001), mean bias −2.03%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Involvement of patients in clinical decision making has been reported to improve health outcomes and adherence to treatment/medication. 20 Nwankwo et al reported that participants ( n = 8) involved in a pilot study for remote capillary sampling agreed that the remote capillary collection process resulted in better decision making and planning of care. 20 Our study findings support those of Nwanko et al, with our participants supporting a greater uptake of this remote collection approach.…”
Section: Discussionmentioning
confidence: 99%